An investigation on the quality of service performance of RapidBET bus service / Noraziyan Abd Aziz - Abd Aziz, Noraziyan (2014)
The Government of Malaysia encourages its people to use public transport instead of private vehicles in order to reduce traffic congestion. However, the failure of public transport to serve their users with high quality of service has discouraged the use of public transport. Therefore, the government through RapidKL introduced RapidBET bus service, which is a new system of transit system during the peak hour only. This study aims to investigate the service quality performance of RapidBET bus services which are RapidBET 1, RapidBET2, RapidBET3 and RapidBET4. In addition, this study focused on the quantifying the customer satisfaction level and determine the mean satisfaction rating on the selected service quality factors of RapidBET bus services. A questionnaire was designed to obtain the customer satisfaction level during the customer satisfaction survey. The selected service quality factors for the customer satisfaction survey include information, scheduling, frequency, hours of service, coverage, travel time, safety, reliability, cost and comfortability. The qualitative data was then transformed by using SPSS software. From the analysis, it showed that most of the RapidBET bus services users’ satisfaction level was average. However, the users chose ticket fare as the highest mean satisfaction rating of service quality while the lowest mean satisfaction ratings were scheduling, frequency and comfortability. The Level of Service (LOS) of each RapidBET bus service quality was also determined. By using the methodology in Transit Capacity and Quality of Service Manual (TCQSM), the performance measure of RapidBET bus service quality was determined. The quantitative data of RapidBET bus service quality was obtained by making observations by taking ride as a passenger in the bus. The selected service quality factors to determine the LOS of RapidBET bus service were frequency, hours of service and travel time. The LOS of each RapidBET bus services were determined to be C, D and F for the service quality factors measured. From this study, it was found that most of the RapidBET bus services quality factors are tolerable and the limited service provided by the operator and the RapidBET bus services is an improvement of the conventional pubhc transportation during the peak hours. As a conclusion, it is important to encourage the study on the service quality performance of our public transport to increase the public transportation demand and achieving the sustainable transportation system in Malaysia